Fundamentals of 5G mobile networks - Rodriguez, Jonathan (Chichester, West Sussex, United Kingdom ; Hoboken, NJ : John Wiley & Sons Ltd, 2015)
Fundamentals of 5G Mobile Networks provides an overview of the key features of the 5th Generation (5G) mobile networks, discussing the motivation for 5G and the main challenges in developing this new technology. This book provides an insight into the key areas of research that will define this new system technology paving the path towards future research and development. The book is multi-disciplinary in nature, and aims to cover a whole host of intertwined subjects that will predominantly influence the 5G landscape, including the future Internet, cloud computing, small cells and self-organ.
Chapter 4 Cooperation for Next Generation Wireless Networks4.1 Introduction; 4.2 Cooperative Diversity and Relaying Strategies; 4.2.1 Cooperation and Network Coding; 4.2.2 Cooperative ARQ MAC Protocols; 4.3 PHY Layer Impact on MAC Protocol Analysis; 4.3.1 Impact of Fast Fading and Shadowing on Packet Reception for QoS Guarantee; 4.3.2 Impact of Shadowing Spatial Correlation; 4.4 Case Study: NCCARQ; 4.4.1 NCCARQ Overview; 4.4.2 PHY Layer Impact; 4.5 Performance Evaluation; 4.5.1 Simulation Scenario; 4.5.2 Simulation Results; 4.6 Conclusion; Acknowledgements; References.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Mobile communication systems -- Technological innovations; Wireless communication systems -- Standards; Mobile communication systems; Mobile communication systems -- Technological innovations; Wireless communication systems -- Standards; TECHNOLOGY & ENGINEERING -- Mechanical; Mobile communication systems -- Technological innovations; Wireless communication systems -- Standards; Electronic books